Kajian Learning Obstacle pada Topik Keliling Segiempat Ditinjau dari Literasi Matematis PISA 2021 - Nabila, Deka Nisa; Sudihartinih, Eyus; Sumiaty, Encum (Edumatica : Jurnal Pendidikan Matematika, 2022)
This research aims to obtain the learning obstacle on the topic of rectangular circumference in terms of Mathematical literacy PISA 2021. This research method is qualitative with a DDR (Didactical Design Research) approach, only at the learning obstacle study stage. Instruments for studying learning obstacles are designed based on PISA 2021 Mathematical literacy. Students' ability to conceptualize the perimeter of a quadrilateral will greatly influence subsequent learning, especially for solving the next topic problem. The participants of this study were six students in one of the private junior high schools in the city of Bandung. Participant 1 (P1) is a class VIII student, the other five participants (P1, P2, P3, P4, P5) are class IX students. The collection technique is done through tests, interviews, and documentation. Based on the study results, it was concluded that there were still some students who did not understand the concept of the perimeter of a quadrilateral in terms of mathematical literacy by PISA 2021. It was known that there were three learning obstacles, namely the connection of the concept of the perimeter of a rectangle with everyday life the ability of students to conceptualize the perimeter of a rectangle related to everyday problems. Days, and Use the formula for the perimeter of a quadrilateral.